Intellectual Capital and Profitability of Islamic Commercial Banks in Indonesia: - Izzuddin, Ahmad; Irfany, Mohammad Iqbal (Review on Islamic Accounting, 2025)
The aim of this study is to investigate the impact of intellectual capital on the profitability of Indonesian Islamic Commercial Banks (BUS), highlighting the significance of intangible assets in enhancing financial performance. Utilizing regression analysis, this study scrutinizes secondary data from BUS's quarterly financial reports between 2015-2020, focusing on the impact of Value Added Intellectual Capital (VAIC), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) on Return on Assets (ROA). The study reveals that VAIC has a significant positive effect on ROA, indicating that effective management of intellectual capital can enhance profitability. Conversely, NPF shows a significant negative impact on ROA, while CAR does not significantly affect ROA. The combined influence of GDP, CAR, NPF, and VAIC explains a substantial portion of the variance in ROA. The scope is confined to BUS within 2015-2020. Future research could extend globally and incorporate more variables to enrich insights. Islamic banks should prioritize the effective management of intellectual capital, particularly human resources, to boost profitability and gain a competitive edge. Regulatory bodies, like the OJK, are recommended to establish policies that support and guide the management of intellectual capital within the banking sector.This study provides novel insights into the significance of intellectual capital in improving the profitability of Indonesian Islamic banks, emphasizing the need for effective management strategies and regulatory policies to enhance the sector's performance and contribution to economic growth.